Prevalence and clinical-pathological features of nevus-associated versus de novo melanoma: a retrospective cross-sectional study of 2806 cases - Caterina Longo; Michela Lai; Simonetta Piana; Giovanni Pellacani; Riccardo Pampena (Mattioli1885, 2022)
Introduction: Nevus-associated melanoma (NAM) accounts for almost one third of all cutaneous melanomas; it is often associated with younger age, trunk location and lower Breslow's thickness compared to de novo melanoma (DNM). Objectives: To define the prevalence of NAM in a tertiary referral Center in Italy and to analyze its distribution according to demographics, clinical and histopathological variables Methods: Data were retrospectively retrieved from the archive of the Pathology Unit from June 2011 to August 2020. NAMs were compared with DNMs according to demographic, clinical and histopathological variables. Results: A total of 2806 consecutive cases of melanoma were excised in 2537 patients. Of these, 431 (15.4%) were NAM. NAM patients were significantly younger than DNM patients (55.1±14.1 vs. 62.0±15.0 years, p<0.001); they were predominantly located on the trunk (64.0% vs. 47.9% of DNMs). Melanoma located on the head and neck, trunk and upper limbs respectively had 2.3 (95%CI:1.2-4.5, p:0.014), 3.2 (95%CI:2.1-5.1, p<0.001) and 3.5 (95%CI:2.0-6.1, p<0.001) more odds to be NAM than those on the lower limbs. Conclusions: Our results confirm the association of NAM with younger age and trunk location. We also demonstrated that body site differences of NAM distribution are enhanced before the sixth decade of life.